Pengaruh Pendekatan Realistic Mathematics Education Terhadap Hasil Belajar Matematika Di Kelas IV SD Negeri 01 Pasirmuncang Tahun Pelajaran 2020/2021 - Rani Yulianti; La Ode Amril (Lembaga Bale Literasi, 2022)
This study aims to find out whether the Realistic Mathematics Education (RME) approach influences the learning outcomes of mathematics in fractions in class IV SDN 01 Pasirmuncang year academic 2020/2021. This research is a quantitative study using the Pretest-Posttest Control Group Design. The research sample consisted of two classes, namely the experimental class which consisted of 35 students and the control class which consisted of 38 students. The Realistic Mathematics Education (RME) approach was used as a treatment for the experimental class, while the control class used a conventional approach. Data collection uses instruments in the form of questions and answers or interviews, as well as tests that have been tested for validity. The learning outcomes in the experimental class (? = 0.002 <0.05), meaning that there is a significant effect of the RME approach on students' mathematics learning outcomes and in the significant control class (? = 0.648 > 0.05), meaning that it does not have the influence of the conventional approach to students' mathematics learning outcomes significantly.